Elite long sprint running: A comparison between incline and level training sessions - Slawinski, J.; Dorel, S.; Hug, F.; Couturier, A.; Fournel, V.; Morin, J.-B.; Hanon, C. (Medicine & Science in Sports & Exercise, 2008)
Purpose: We compared incline and level training sessions as usually used in elite 400-m runners through stride kinematics and muscular activity measurements.